POTENTIAL USAGE OF NEW ANTITUSSIVE MEDICATIONS «BRONCHOTUS FORTE – ELIXIR» AND «AMBRORITE – TABLETS» DURING THE NATURAL HISTORY OF COVID-19 - Tursunova M. Kh. (Scholars Digest Publishing, 2024)
Cough is the most frequent symptom of the infection of the 21st century – COVID-19. Cough occurs in 70-80% of patients, being the second most frequent symptom caused by SARS – CoV-2. In this regard, interest arose in the development of new combinations of medications that have antitussive, mucolytic and expectorant properties, such as «Bronchotus forte - elixir» and «Ambrorite - tablets». The purpose of the study is to determine the pharmacological effects of new antitussives «Bronchotus forte - elixir» and «Ambrorite - tablets». The investigation of the efficacy of the medications were conducted, using known drugs, that are close in composition and accredited in the Republic of Uzbekistan according to the common methods of investigations. The experiments were conducted at Testing laboratory (ISO 17025) at «METHPHARM» LLC. The experiment was conducted on healthy sexually mature white rats and guinea pigs of both sexes which were quarantined for 14 days after their adaptation period in the vivarium, physical conditions of which were monitored for 4-5 days. To investigate the antitussive effect, guinea pig cough model was used; citric acid-induced coughing was modelled. Mucolytic and expectorant effects were determined by the amount of excreted sputum by white rats, influenced by the studied medications. Statistical processing of the obtained data was carried out with the help of software package Microsoft Excel 2007 (for Windows 7), the reliability of which was evaluated by the Student's t-test. The results showed that the investigated medication «Bronchotus forte - elixir» has a pronounced antitussive effect and is not inferior to the known medication «Codelac® Broncho with thyme - elixir» in terms of the abovementioned property, besides it has a pronounced mucolytic effect. The medication «Ambrorite – tablets» possesses pronounced expectorant effect and is not inferior to the brand-name medication «Ambroxol», produced by «MERRYMED FARM» LLC, Uzbekistan, in terms of efficacy. Obtained data allows the medications to be recommended for the clinical practice as a treatment of cough during the natural history of COVID-19.
Keywords: cough, COVID-19, antitussives, mucolytic effect, expectorant effect, antitussive effect.